[(1)N,(12)N]Bis(Ethyl)-cis-6,7-Dehydrospermine: a New Drug for Treatment and Prevention of Cryptosporidium parvum Infection of Mice Deficient in T-Cell Receptor Alpha - Waters, W. R. (American Society for Microbiology, 2000)
Cryptosporidium parvum infection of T-cell receptor alpha (TCR-α)-deficient mice results in a persistent infection. In this study, treatment with a polyamine analogue (SL-11047) prevented C. parvum infection in suckling TCR-α-deficient mice and cleared an existing infection in older mice. Treatment with putrescine, while capable of preventing infection, did not clear C. parvum from previously infected mice. These findings provide further evidence that polyamine metabolic pathways are targets for new anticryptosporidial chemotherapeutic agents.